2016
DOI: 10.1038/srep26610
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid: diacylglycerol acyltransferase contributes to the conversion of membrane lipids into triacylglycerol in Myrmecia incisa during the nitrogen starvation stress

Abstract: In addition to the Kennedy pathway for de novo biosynthesis, triacylglycerol (TAG), the most important stock for microalgae-based biodiesel production, can be synthesized by phospholipid: diacylglycerol acyltransferase (PDAT) that transfers an acyl group from phospholipids (PLs) to diacylglycerol (DAG). This study presents a novel gene that encodes PDAT from the green microalga Myrmecia incisa Reisigl H4301 (designated MiPDAT ). MiPDAT is localized on the plasma membrane (PM) via the agroinfiltration of tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
(99 reference statements)
0
26
0
Order By: Relevance
“…9). In Chlamydomonas and other microalgae like Myrmecia incisa, the increase in PDAT transcript abundance under N deprivation reflected both the reduction in membrane phospholipid content and increased TAG accumulation (Yoon et al, 2012;Liu et al, 2016b). The involvement of PDAT in membrane recycling was also directly confirmed in Chlamydomonas, where a knockdown of PDAT resulted in the increase of membrane lipid content and decreased levels of TAG (Yoon et al, 2012), although in this case the enzyme uses lipids other than phosphatidylglycerol, which is absent in Chlamydomonas.…”
Section: Divergent Pathways Of Fa Recycling Are Active During N Deprimentioning
confidence: 82%
“…9). In Chlamydomonas and other microalgae like Myrmecia incisa, the increase in PDAT transcript abundance under N deprivation reflected both the reduction in membrane phospholipid content and increased TAG accumulation (Yoon et al, 2012;Liu et al, 2016b). The involvement of PDAT in membrane recycling was also directly confirmed in Chlamydomonas, where a knockdown of PDAT resulted in the increase of membrane lipid content and decreased levels of TAG (Yoon et al, 2012), although in this case the enzyme uses lipids other than phosphatidylglycerol, which is absent in Chlamydomonas.…”
Section: Divergent Pathways Of Fa Recycling Are Active During N Deprimentioning
confidence: 82%
“…Moreover, it has been reported that some PDATs located on the plasma membrane (e.g. MiPDAT, and RcPDAT2) ( Liu et al, 2016 ; Pan et al, 2015 ), while others are located in chloroplasts (e.g. CrPDAT) ( Yoon et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with DGATs, relatively little functional information is available on PDATs ( Pan et al, 2015 ), although PDATs have been identified from yeast ( Saccharomyces cerevisiae ; encoded by LOR1 gene; Dahlqvist et al, 2000 ), Arabidopsis (AtPDAT1 and AtPDAT2; Ståhl et al, 2004 ), flax ( Linum usitatissimum ) (LuPDAT1 and LuPDAT2; Pan et al, 2013 ), castor bean (Ricinus communis) (RcPDAT1 and RcPDAT2; Kim et al, 2011 ), two green microalga Chlamydomonas reinhardtii (CrPDAT; Yoon et al, 2012 ) and Myrmecia incise ( MiPDAT ; Liu et al, 2016 ). In Arabidopsis, PDAT1 was not a key contributor of TAG content in developing seeds ( Mhaske et al, 2005 ), but exhibited overlapping function with DGAT1 in TAG biosynthesis in seed and pollen grain development ( Zhang et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering medium chain fatty acids such as 12:0 are rarely incorporated into the sn-2 of PtdCho, which is the substrate of PDAT, it is likely that the relative use of PDAT and DGAT in TAG biosynthesis in leaves is dependent on the substrates and acyl flux conditions within the cell (Bates, 2016). Besides Arabidopsis, PDAT genes have also been identified and characterized in various plant and microalgal species, including castor (Kim et al, 2011;van Erp et al, 2011), flax (Pan et al, 2013), Camelina sativa (Aznar-Moreno and Yuan et al, 2017), green algae C. reinhardtii (Yoon et al, 2012), and green algae Myrmecia incise (Liu et al, 2016b). It should be noted that the PDAT nomenclature in the literature lacks consistency.…”
Section: Acyl-coa-independent Formation Of Tagmentioning
confidence: 99%
“…This is also supported by a recent detailed lipidomic analysis of developing B. napus seeds, in which the relative contributions of DGAT and PDAT were predicted based on the patterns of their molecular substrates (Woodfield et al, ). Furthermore, it has also been recently suggested that PDAT appears to function in stress responses in Arabidopsis (Mueller et al, ), C. sativa (Yuan et al, ), and green algae (Liu et al, ; Yoon et al, ). For instance, PDAT1‐mediated TAG accumulation was found to increase the heat resistance of Arabidopsis seedlings (Mueller et al, ).…”
Section: Introductionmentioning
confidence: 99%